SKRINING ANEMIA MELALUI PEMERIKSAAN LABORATORIUM PADA MASYARAKAT PESISIR DESA MEKAR KECAMATAN SOROPIA - Sari, Julianti Isma; Orno, Theosobia Grace; Hasan, Fonnie Esther (Universitas Pattimura, 2023)
Anemia was detected from laboratory tests with hemoglobin, hematocrit and erythrocyte levels below the reference value. Anemia can be detected with Point of Care Testing method using and is effective for conducting examinations in areas with a relatively small number of health facilities. The type of method used is analytic observation. This community service aims to screen for anemia by knowing hemoglobin and hematocrit levels. The results of the examination showed that from 50 respondents, the average hemoglobin level had a result below the reference value of 12.0 – 17.0 g/dl and the hematocrit value having a result below the reference value of 37-48%. The average hemoglobin value for men is 12.0 g/dl and for women is 11.9 g/dl. The average hematocrit value for both men and women is 35%. %. With anemia screening conducted, the public can find out hemoglobin and hematocrit levels as an effort to prevent anemia